Perbedaan Dataran Tinggi dan Dataran Rendah terhadap Keberagaman Spesies Anopheles spp. di Provinsi Nusa Tenggara Timur - Mutiara Widawati; Made agus nurjana; Rika mayasari (Loka Litbang Kesehatan Pangandaran, 2018)
Ecological studies on the vector species diversity usually focused on particular habitats and not a comparative study. Therefore, a research has been carried out to see the variation from one of many aspects which affects the condition of a habitat such as altitude. This study aimed to determine the Anopheles spp. species diversity between highland and lowland captured in the research of Vektora 2015-2016 in East Nusa Tenggara Province, Indonesia. This study is a further analysis of Vektora Research Data from 2015 to 2016 in East Nusa Tenggara Province. The population in this study is the whole Anopheles spp. in East Nusa Tenggara Province from 2015-2016. The sample is Anopheles species caught on Vektora. The variables used in this study are categorical variables of highland or lowland, Anopheles species and dominance index. This study results indicate that there is a significant difference in the number of Anopheles obtained per species between the lowlands and the highlands. The number of Anopheles found in the lowland is higher than in the highland. The lowland have more Anopheles species variation compare to the highland. Anopheles annularis is the most commonly Anopheles found in the lowlands whereas Anopheles vagus is the most commonly Anopheles found in the highlands.